St. Louis MetroLink: reframing public transit space - Grogan, Heather (Kansas State University, 2011)
People often move through public transit space only recognizing the functional qualities. In such an environment we become faceless bodies moving through the landscape. As our environments become increasingly functional, so do humans—we cycle anonymously between work and home with little spontaneous interaction occurring in between. The daily routine is executed in nonplace: “Where once there were places we now find nonplaces. In real places the human being is a person. He or she is an individual, unique and possessing a character. In nonplaces, individuality disappears. In nonplaces, character is irrelevant and one is only the customer or shopper, client or patients, a body to be seated, and address to be billed, a car to be parked” (Oldenburg 1989, 205). The Maplewood light rail station in St. Louis County, Missouri is an example of nonplace. Although functional, the landscape lacks character. In order to combat nonplace sociologist Ray Oldenburg suggests that we cultivate third places—liminal spheres between home and work that facilitate informal social interaction. A major component of third place is user accessibility. Therefore, the ability to physically and mentally access public transit space will be investigated as a design dilemma. Through the reframing of physical and mental accessibility the Maplewood MetroLink station will evolve into a third place capable of supporting informal social interaction. In order to understand the factors influencing social interaction in public transit space, five precedents were examined using the Project for Public Spaces definition of “place.” Characteristics found to promote social activity include linkages, flexibility, imageability and social infrastructure. The factors were further defined as ‘mental’ or ‘physical’ accessibility which were then used to analyze the Maplewood MetroLink station. After examining physical and mental accessibility at the Maplewood MetroLink station, a design solution was proposed. The design encourages users to pause and interact with each other and the landscape in a highly mobile environment.
Keywords: third place; public transit; Aesthetics (0650); Landscape Architecture (0390); Transportation (0709)